2009
DOI: 10.1007/s00122-008-0951-8
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed genes during malting and correlation with malting quality phenotypes in barley (Hordeum vulgare L.)

Abstract: Breeding for malting quality is an important goal of malting barley breeding programs. Malting quality is a complex phenotype that combines a large number of interrelated components, each of which shows complex inheritance. Currently, only a few genes involved in determining malting quality have been characterized. We combined transcript proWling with phenotypic correlations to identify candidate genes for malting quality. The Barley1 GeneChip ® array containing 22,792 probe sets was used to conduct transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Differences in expression levels of histones have been found during seed germination in barley (Potokina et al 2002) and their presence in this study could be due to differences in the cell division cycle activity between both genotypes. Many genes recently identified by Lapitan et al (2009) as correlated to malting quality phenotypes coded for proteins involved in defense and stress response, among which jasmonate-induced proteins were the most abundant ones. Other previous studies on germinating seeds also identified these proteins (Watson and Henry, 2005;White et al 2006).…”
Section: Malting Quality Footprintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in expression levels of histones have been found during seed germination in barley (Potokina et al 2002) and their presence in this study could be due to differences in the cell division cycle activity between both genotypes. Many genes recently identified by Lapitan et al (2009) as correlated to malting quality phenotypes coded for proteins involved in defense and stress response, among which jasmonate-induced proteins were the most abundant ones. Other previous studies on germinating seeds also identified these proteins (Watson and Henry, 2005;White et al 2006).…”
Section: Malting Quality Footprintsmentioning
confidence: 99%
“…Large-scale gene expression technologies such as cDNA-and oligonucleotide-based arrays, and serial analysis of gene expression (SAGE) have proved to be useful to conduct transcript profiling during germination and malting (Lapitan et al 2009;Potokina et al 2002Potokina et al , 2004Watson and Henry 2005;White et al 2006), and to identify candidate genes for malting quality (Lapitan et al 2009;Potokina et al 2004Potokina et al , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Barley (Hordeum vulgare L.) is one of the most important cereal crops in the world, ranking fourth after wheat, maize, and rice in terms of production (Lapitan et al 2009). It is an important food grain and malting crop in the Ethiopian highlands, with malting barley a major source of income for smallholder farmers (Yirga et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was a positive correlation between DNA sequence polymorphisms and gene expression differences. Although this is probably the most exhaustive study of gene expression diversity, other groups have also mentioned differences in gene expression in five maize inbred lines [16] and four barley varieties [17]. The percentage of the transcriptome showing variation in gene expression was much smaller in these two cases, approximately 1.6-6% in maize and 0.1-1.5% in barley.…”
Section: Introductionmentioning
confidence: 99%